PENGEMBANGAN GAME EDUKASI BERBASIS FLIPBOOK PADA PEMBELAJARAN PKN UNTUK MENUMBUHKAN NILAI-NILAI PROFIL PANCASILA DI SEKOLAH DASAR - Lubis, Renni Ramadhani; Parinduri, Wina Mariana; Rambe, Titin Rahmayanti; Rambe, Nurhamimah (Universitas Negeri Medan, 2024)
This research aims to develop a flipbook based educational game to foster the values of Pancasila student profiles. This research is research and development. This research uses the ADDIE development model. This research was carried out at SD IT Bintang Langkat. The subjects in this research were 20 class IV students. Data collection techniques are observation, questionnaires and tests. The data analysis used in this research is: (1) analysis of the feasibility of flipbook based educational games, (2) analysis of the effectiveness of flipbook based educational games. Based on the validation results, it is known that the material expert validation results with a percentage of 89.23% are categorized as very feasible. Linguist validation results with a percentage of 92.30% are categorized as very feasible. The media expert validation results with a percentage of 96.66% were categorized as very feasible. The results of expert practitioner validation with a percentage of 88.34% are categorized as very feasible. The results of the pretest revealed that 15 students completed and five students did not complete, the learning outcomes of the students who completed were a percentage of 55%. Meanwhile, the results of the posttest test showed that 17 students completed and 3 students did not complete, the learning outcomes of students who completed were 77%.